Cooperative Adsorption of Metal‐organic Complexes on CsPbI2Br Perovskite Surface for Photovoltaic Efficiency Exceeding 17 %. Issue 23 (10th October 2022) - Shi, Yiheng; He, Jingjing; Lian, Huijun; Liu, Xinyi; Yuan, Haiyang; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract: Inorganic perovskite solar cells have attracted wide attention due to their excellent thermodynamic stability and suitable bandgap as the top absorber materials for tandem solar cells. However, the power conversion efficiencies (PCEs) of the perovskite cells can be considerably limited by the non‐radiative energy loss caused by grain boundaries and surfaces. Here, the synergistic functionalization of CsPbI2 Br perovskites was demonstrated by using a metal‐organic complex. Experimental and theoretical studies revealed that the adsorption energy of the passivator could be a good descriptor to evaluate the surface passivation effect. The cooperative adsorption could eliminate the unsaturated surface sites, reduce the surface energy, and thus benefit device performance. The CsPbI2 Br solar cells passivated by zinc diethyldithiocarbamate showed a champion power conversion efficiency of 17.15 % and retained 94 % of their initial efficiency after working under 1 sun illumination for 720 h in N2 atmosphere. Abstract : Passivation : A cooperative adsorption strategy is proposed in this study to passivate CsPbI2 Br perovskite solar cells. With a simple wet‐chemical process, cationic and anionic‐type passivators contribute to the high performance of solar cells, boosting the power conversion efficiency to 17.15 %.